2015
DOI: 10.1002/jrs.4823
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of G-quadruplex conformations using Raman and polarized Raman spectroscopy

Abstract: G‐quadruplexes (G4s) are four‐stranded DNA structures formed within nucleic acid sequences that are rich in guanines. G4 formation within DNA strands is believed to have significant biological relevance for the control of cell replication and gene expression. Therefore, the development and validation of experimental techniques that can easily and reliably characterize G4 structures under biologically relevant measurement conditions, like Raman spectroscopy, are desirable for G4‐targeted structure based drug de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 65 publications
(205 reference statements)
1
26
0
Order By: Relevance
“…Friedman and Terentis reported the analysis of G‐quadruplex conformations using Raman and polarized Raman spectroscopy. Their results support the previously proposed antiparallel (TBA), antiparallel and hybrid (HT), and parallel with double‐chain reversal (DCR) loop (MycL1) structures . Hernandez et al demonstrated that all characteristic Raman markers of tyrosine and tyrosinate originate from phenol ring fundamental vibrations.…”
Section: Biosciencessupporting
confidence: 78%
See 1 more Smart Citation
“…Friedman and Terentis reported the analysis of G‐quadruplex conformations using Raman and polarized Raman spectroscopy. Their results support the previously proposed antiparallel (TBA), antiparallel and hybrid (HT), and parallel with double‐chain reversal (DCR) loop (MycL1) structures . Hernandez et al demonstrated that all characteristic Raman markers of tyrosine and tyrosinate originate from phenol ring fundamental vibrations.…”
Section: Biosciencessupporting
confidence: 78%
“…Their results support the previously proposed antiparallel (TBA), antiparallel and hybrid (HT), and parallel with double-chain reversal (DCR) loop (MycL1) structures. [56] Hernandez et al demonstrated that all characteristic Raman markers of tyrosine and tyrosinate originate from phenol ring fundamental vibrations. Their Raman data collected from free amino acid and peptide chains permit assignment of the seven markers located at approximately 1,616, 1,606, 1,210, 1,178, 850, 830, and 643 cm −1 to tyrosine.…”
Section: Biomoleculesmentioning
confidence: 99%
“…Conventional nonresonant Raman spectroscopy was first intensively used to study G‐quadruplexes in the Thomas lab in the mid‐1990 . Later several other articles, including ours, appeared . The decisive advantage of nonresonant Raman spectroscopy is its spectral richness and the ability to study nucleic acids samples in solution over a wide range of DNA concentrations, as a function of various physicochemical factors such as temperature or ionic strength, starting at concentrations typical of NMR measurements (and still accessible by CD spectroscopy) up to very high concentrations not readily accessible by other methods .…”
Section: Introductionmentioning
confidence: 99%
“…[36][37][38][39][40][41] Later several other articles, including ours, [16] appeared. [42,43] The decisive advantage of nonresonant Raman spectroscopy is its spectral richness and the ability to study nucleic acids samples in solution over a wide FIGURE 1 Schematic sketch of the G-quadruplex structures of wt (i.e. AG 3 (T 2 AG 3 ) 3 ) in Na + [24], and ap19 [18] and ap7-13-19 in K + [19] with the positions of adenine abasic lesions (within the original sequence of wt) denoted by stars.…”
Section: Introductionmentioning
confidence: 99%
“…For that experiment, Raman tensors were obtained from polarized Raman analyses of oriented specimens of EtBr (single crystal) and DNA (hydrated fiber). Polarized RS is also applied to DNA quadruplexes and telomeres identification and characterization [162].…”
Section: Raman Spectroscopy In Dna Structural Investigationsmentioning
confidence: 99%